PERBANDINGAN AKTIVITAS ANTIBAKTERI BERBAGAI MINYAK ATSIRI TERHADAP PERTUMBUHAN STAPHYLOCOCCUS AUREUS - Violantika, Nadia; Yulian, Muammar; Nuzlia, Cut (AMINA, 2020)
Essential oil is a type of oil that is produced from various parts of the plant, is a thick liquid at room temperature, and evaporates easily, giving it a distinctive aroma. One of the essential oils is used as an antibacterial compound. This study aims to measure the variation in the deposition of various types of essential oils as an inhibitor of the growth of Staphylococcus aureus bacteria. This research method is a Literature Review by examining the use of various concentrations of various types of essential oils to inhibit the growth of Staphylococcus aureus bacteria. The best inhibition of growth of Staphylococcus aureus bacteria was obtained in the essential oil of basil leaves at a concentration of 4% with inhibition of 40.35 mm. Meanwhile, the lowest inhibition of growth of the Staphylococcus aureus bacteria for black fungus isolates was obtained at a concentration of 0.5% with an average inhibition zone of 1.16 mm.